Sex, symptom, and premorbid social functioning associated with perceptual organization dysfunction in schizophrenia - Joseph, Jamie; Bae, Grace; Silverstein, Steven M. (Frontiers in Psychology, 2013)
Impairments in visual perceptual organization abilities are a repeatedly observed cognitive deficit in schizophrenia. These impairments have been found to be most prominent among patients with histories of poor premorbid social functioning, disorganized symptoms, and poor clinical outcomes. Despite the demonstration of significant sex differences for these clinical factors in schizophrenia, the extent of sex differences for visual perceptual organization in schizophrenia is unknown. Therefore, we investigated the extent to which previously known correlates (premorbid social sexual functioning and disorganized symptoms) and a novel factor (participant sex) accounted for performance on two perceptual organization tasks (contour integration and Ebbinghaus illusion) that have previously demonstrated sensitivity to schizophrenia. We also determined the relative degree to which each of these factors predicted task scores over and above the others. Schizophrenia patients (N = 109, 43 female) from different levels of care were ascertained. Female patients demonstrated higher contour integration scores, but lower performance on the context sensitivity index of the Ebbinghaus illusion, compared to males. Contour integration performance was significantly associated with poorer premorbid adolescent social sexual functioning and higher levels of disorganized symptoms, supporting past results that indicate a relationship among poor premorbid social sexual functioning, disorganized symptoms, and visual perceptual abnormalities in schizophrenia. However, analyses of Ebbinghaus illusion performance suggests there is a complex relationship among patient sex, clinical factors and perceptual abilities with relatively intact bottom-up grouping processes in females, but greater problems, compared to males with more top-down mediated context sensitivity. Therefore, sex differences may be an important consideration for future studies of visual perceptual organization in schizophrenia.